2022
DOI: 10.3389/fcvm.2022.867012
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Survival of Adult Patients With Atrial Septal Defect With Regards to Defect Closure and Pulmonary Hypertension

Abstract: BackgroundAtrial septal defect (ASD) is the most common congenital heart disease (CHD) in adults and pulmonary hypertension (PH) is an established risk factor. A decision whether to perform ASD closure, especially in elderly patients with PH, is a complex dilemma. The aim of our study was to compare long-term survival in patients with closed and open ASD.MethodsA retrospective cohort study was performed on 427 patients with ASD (median age at diagnosis 38 years, IQR 18–56) out of which 186 patients (44%) manif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Several studies demonstrated that mortality is higher for ASD patients than for the general population, and Eisenmenger syndrome, age at diagnosis, and pulmonary hypertension (PH) are independent positive predictors of mortality, while ASD closure is a positive independent predictor of survival [ 54 , 55 ]. SCD is a leading cause of death among adults with CHD, and accounts for up to 25% of deaths [ 56 , 57 , 58 ].…”
Section: Long-term Survival and Risk Of Scd In Patients With Asdmentioning
confidence: 99%
“…Several studies demonstrated that mortality is higher for ASD patients than for the general population, and Eisenmenger syndrome, age at diagnosis, and pulmonary hypertension (PH) are independent positive predictors of mortality, while ASD closure is a positive independent predictor of survival [ 54 , 55 ]. SCD is a leading cause of death among adults with CHD, and accounts for up to 25% of deaths [ 56 , 57 , 58 ].…”
Section: Long-term Survival and Risk Of Scd In Patients With Asdmentioning
confidence: 99%
“…In the case of ASD, the abnormal blood shunt from left to right occurs and the overload of the right heart and pulmonary artery (PA) emerges. The pressure in PA increases and in most of the cases PAH develops, but also hyperkinetic pulmonary hypertension can occur, which is reversible after the closure of the defect and has a good long term survival [ 4 ]. Rarely, in about 1% of patients with congenital ASD, Eisenmenger’s syndrome occurs because of the progression of PAH [ 5 ].…”
Section: Introductionmentioning
confidence: 99%